Nationalist movements and the state in Canada and France : ethno-territorial protest movements in Québec and Corsica, 1960 to 1995 - Lammert, Christian (2001)
Since the early 1960s ethno-territorial movements have increasingly challenged established patterns of political integration in western democracies. The purpose of this paper is to compare the formation and different paths of development of such nationalist movements in Quebec (Canada) and Corsica (France). The paper presents a brief outline of an argument more fully developed in a study on the two cases. After a short introduction I will first discuss theoretical aspects of minority nationalism. Secondly, I will try to give an overview over major findings and conclusions of my study.